A Study on Bio-Coke Production—The Influence of Biochar Addition to the Coking Blend on Bio-Coke Quality Parameters - Michał Rejdak; Michał Książek; Małgorzata Wojtaszek-Kalaitzidi; Anna Rodź; Bartosz Mertas; Sten Yngve Larsen; Piotr Szecówka (Energies)
Carbon dioxide is emitted in several industrial processes and contributes to global warming. One of the industries that is considered a significant emitter is metallurgy. Therefore, it is necessary to search for and implement methods to reduce its emissions from metallurgical processes. An alternative option to the use of conventional coke, which is produced solely from fossil coal, is the utilization of bio-coke. The production of bio-coke involves the use of coking coal and the incorporation of biomass-derived substances such as biochar (charcoal). The article presents the results of the research on the influence of the biochar addition on the structural, textural, and technological properties of produced bio-coke. Research on the production and analysis of the properties of the obtained bio-coke aimed at assessing the potential possibilities of applying it in the process of a carbothermal reduction of manganese ore in order to smelt ferroalloys. Studies have shown that biochar addition to the coking blend in an amount of up to 20% allows a bio-coke characterized by properties enabling the mentioned use to be obtained. Bio-coke was characterized by higher CO2 reactivity index (CRI), lower post-reaction strength (CSR), and higher reactivity to synthetic manganese ore than regular metallurgical coke. In the context of industrial applications of bio-coke, it is necessary to verify its production and use on a pilot and industrial scale.